Association Between Menstrual Patterns and Adverse Pregnancy Outcomes in Patients With Polycystic Ovary Syndrome - Yu, Ting; Wu, Di; Cao, Yurong; Zhai, Jun (Frontiers in Endocrinology, 2021)
Objective: To investigate the results of in vitro fertilization among polycystic ovary syndrome (PCOS) patients using the long-acting long protocol regarding the relationship between menstrual patterns and adverse pregnancy outcomes. Design: Retrospective cohort study Setting: University-affiliated reproductive medical center Background: The menstrual patterns of patients with PCOS is considered related to metabolism; however, no study has analyzed the outcome of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) in patients with PCOS who have different menstrual patterns. This study aimed to observe the outcomes of IVF/ICSI in patients with PCOS with different menstrual patterns who used the long-acting long protocol. Methods: This was a retrospective analysis in the first cycle of IVF/ICSI at the Reproductive Medicine Center of the First Affiliated Hospital of Zhengzhou University from January 2017 to December 2019. In total, 1834 patients with PCOS were classified into the regular menstruation group (n=214), the oligomenorrhea group (n=1402), and the amenorrhea group (n=218). Results: PCOS patients who used the long-acting long protocol of IVF/ICSI had similar clinical pregnancy rates and live birth rates despite having different menstrual patterns. The overall incidence of adverse pregnancy outcomes, including abortion, spontaneous preterm birth (sPTB), gestational diabetes(GDM), hypertensive disorder inpregnancy (HDP), and premature rupture of membranes(PROM, was significantly higher in the amenorrhea group than in the regular menstrual and oligomenorrhea groups (25.88% vs. 30.41% vs. 43.69%; P = 0.013). Additionally, the rates of GDM (2.35% vs. 6.10% vs. 13.79%; P=0.015) and macrosomia (5.26% vs. 10.94% vs. 18.39% ; P=0.026) in the amenorrhea group were significantly higher than those in the other two groups. Correction for confounding factors showed that menstrual patterns are related to the occurrence of adverse pregnancy outcomes. Amenorrhea is an independent risk factor for adverse pregnancy outcome (OR [odds ratio]: 2.039, 95% CI [confidence interval]: 1.087-3.822), GDM (OR: 5.023, 95% CI: 1.083–23.289), and macrosomia (OR: 4.918, 95% CI: 1.516–15.954). Conclusions: IVF/ICSI can achieve similar pregnancy and live birth rates in PCOS patients with different menstrual patterns. However, the overall incidence of adverse pregnancy outcomes in PCOS patients with amenorrhea is higher than that in patients with regular menstruation or oligomenorrhea.